The in‐hospital administration of sacubitril/valsartan in acute myocardial infarction: A meta‐analysis - Gianluca Di Pietro; Riccardo Improta; Paolo Severino; Andrea D'Amato; Lucia Ilaria Birtolo; Ovidio De Filippo; Antonio Lattanzio; Raffaele De Cristofaro; Giacchino Galardo; Fabrizio D'Ascenzo; Roberto Badagliacca; Gennaro Sardella; et al. (ESC Heart Failure)
Abstract There is a need to address the evidence gap regarding the in‐hospital administration of sacubitril/valsartan in acute myocardial infarction patients. After searching MEDLINE, Google Scholars and Scopus, a random‐effects meta‐analysis of randomized controlled trials comparing the in‐hospital administration of the angiotensin receptor‐neprilysin inhibitors (ARNis) versus the standard therapy in patients with reduced heart failure due to myocardial infarction was performed. The primary outcome was major adverse cardiovascular events. All‐cause mortality, cardiac death, rehospitalization for heart failure, non‐fatal myocardial infarction (MI), changes in left ventricular ejection fraction, left ventricular volumes, N terminal pro brain natriuretic peptide and adverse events were the secondary endpoints. Nine studies (eight randomized controlled trials and one echo‐substudy) with a total 6597 individuals (angiotensin‐converting enzyme inhibitor/angiotensin receptor blocker: 3300 patients vs. ARNis: 3297 patients) were included for quantitative analysis. Median follow‐up was 6 months. Patients receiving an in‐hospital coadministration of ARNi had a lower risk of major cardiovascular event [odds ratio (OR) 0.45, 95% confidence interval (CI) 0.32–0.63, P < 0.0001] and lower rate of repeat rehospitalization for heart failure (OR 0.40, 95% CI 0.26–0.62, P < 0.0001), compared with a standard regimen. Additionally, left ventricle volumes were significantly lower in the ARNi group [left ventricular end‐diastolic volume, mean difference (MD) 11.48 mL, 95% CI 6.10–16.85, P < 0.0001; left ventricular end‐systolic volume, MD 7.09 mL, 95% CI 2.89–11.29, P = 0.0009] with a significant change in left ventricular ejection fraction (MD 3.07, 95% CI 1.61–4.53, P < 0.0001), compared with standard therapy. No significant differences were observed in terms of cardiac death, all cause of mortality, non‐fatal myocardial infarction and N terminal pro brain natriuretic peptide. Higher rates of iatrogenic hypotensive events were observed in the ARNi group compared with the standard therapy (OR 1.42, 95% CI 1.26–1.60, P value < 0.00001). In patients with acute myocardial infarction related heart failure, the in‐hospital administration of ARNis was associated with a reduced risk of major cardiovascular events and re‐hospitalization for heart failure, as well as cardiac remodelling, but higher rates of hypotensive events compared with standard therapy.